2020
DOI: 10.1002/aisy.202000079
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Photoelectric Memristor Gates for In Situ Image Compression

Abstract: Integrated circuits designed to perform mathematical operations, such as Fourier transforms and matrix multiplications, in artificial visual perception and intelligent image processing are mainly constructed of conventional logic gates. However, Boolean logic is probably not the most optimal approach for brain‐inspired computing due to the fuzzy nature of biologic neural networks. This work demonstrates an application based on programmable fuzzy‐logic gates capable of combined photoelectric computations. Such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The image compression could be achieved by taking the generated pulses through a multilayer voltage sensor as input, mapping the image pixels into memristive conductance through the computational array, and then storing them in the other two crossbar arrays. The research conducted by Berco et al in 2020 proposed a programmable photoelectronic memristor gate circuit, which could perform state switching between optical and electrical signals, to realize in-situ image compression [42]. A research team from Dalian University of Technology [43] designed the simplest fractional-order chaotic memory circuit that identified pseudo-random sequences in image compression through phase diagrams, Lyapunov exponential spectra, and bifurcation diagrams, which achieved image compression for the second time and reduced the storage costs significantly.…”
Section: Image Compression Based On Memristive Systemsmentioning
confidence: 99%
“…The image compression could be achieved by taking the generated pulses through a multilayer voltage sensor as input, mapping the image pixels into memristive conductance through the computational array, and then storing them in the other two crossbar arrays. The research conducted by Berco et al in 2020 proposed a programmable photoelectronic memristor gate circuit, which could perform state switching between optical and electrical signals, to realize in-situ image compression [42]. A research team from Dalian University of Technology [43] designed the simplest fractional-order chaotic memory circuit that identified pseudo-random sequences in image compression through phase diagrams, Lyapunov exponential spectra, and bifurcation diagrams, which achieved image compression for the second time and reduced the storage costs significantly.…”
Section: Image Compression Based On Memristive Systemsmentioning
confidence: 99%
“…The exploration of diversified multifunctional electronic devices is therefore a topic of intense with respect to big data, digital communication and energy sensing 4–6 . Boolean logic gates are the building blocks of computing and digital information process; for example, “AND” or “OR” logic gates can be used for address recognition, data integrity checking, 7 and can be used to form memristors 8 . “NOT” logic gates can be also used as inverters and switches.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30–33 ] Followed by a three‐input material, nonimplication and logic conjunction gate constructed out of two memristors and a pull‐down resistor was demonstrated that may be used to perform in situ image compression. [ 34 ]…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] Followed by a three-input material, nonimplication and logic conjunction gate constructed out of two memristors and a pull-down resistor was demonstrated that may be used to perform in situ image compression. [34] The biologic retina consists of light-sensitive rods and cones. Photons (with wavelengths in the visual range) stimulate them to produce excitations that are converted into electric signals and propagated by synaptic junctions in bipolar cells.…”
mentioning
confidence: 99%